Weak coupling of observed surface PM2.5 in Delhi-NCR with rice crop residue burning in Punjab and Haryana - Poonam Mangaraj; Yutaka Matsumi; Tomoki Nakayama; Akash Biswal; Kazuyo Yamaji; Hikaru Araki; Natsuko Yasutomi; Masayuki Takigawa; Prabir K. Patra; Sachiko Hayashida; Akanksha Sharma; A. P. Dimri; et al. (npj Climate and Atmospheric Science)
Abstract Air pollution impacts on human health are of serious concern in northern India, and over the Delhi National Capital Region (NCR) in particular. The Kharif crop residue burning (CRB) is often blamed for degradation of Delhi-NCR’s seasonal air quality. However, the concentration of fine particulate matter (PM2.5) remained stable in Delhi, while the fire detection counts (FDCs) from satellites over Punjab and Haryana declined by 50% or more during 2015–2023. We measured PM2.5, carbon monoxide (CO) and related parameters over Delhi-NCR, Haryana and Punjab from a network of 30 low-cost sensors (CUPI-Gs) in a selected period (September–November) of 2022 and 2023. Measured PM2.5 showed lower concentration in 2023 compared to 2022 at Punjab and Haryana sites, in compliance with FDC reductions. Using the CUPI-G measurements, airmass trajectories, particle dispersion and chemical-transport model simulations, we show that the CRB emissions over Punjab contributed only a meagre ~14% to the overall PM2.5 over Delhi-NCR during October-November 2022. This indicates that there exists only a very weak coupling between PM2.5 mass over Delhi-NCR and the CRB over Punjab, highlighting the effectiveness of the Graded Response Action Plan (GRAP) in controlling air pollution in the region.